2011
DOI: 10.1074/jbc.m110.200907
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Transforming Growth Factor-β-activated Kinase 1 (TAK1)-c-Rel and Interferon Regulatory Factor 4 (IRF4) Pathways in Human T Cell Lymphotropic Virus 1-transformed T helper 17 Cells Producing Interleukin-9

Abstract: Investigation of helper T cell markers in HTLV-1-transformed cell lines demonstrated thatHuT-102 has an IL-9-producing Th17 phenotype. We confirmed the vital role of retinoic acid-related orphan receptor C, a Th17 transcription factor, in the expression of IL-17. Interferon regulatory factor 4 (IRF4), a transcription factor overexpressed in all HTLV-1-infected cells, regulated IL-17 and IL-9 concomitantly. We further demonstrated a novel pathway for the regulation of Tax-induced cytokines, IL-9 and IL-6, throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Interestingly, the HTLV-transformed cell line Hut-102 has an IL-9-producing Th17 phenotype. It is shown that in this cell, specific knockdown of NF-B protein c-Rel results in reduced IL-9 production (77). We have also found that NFAT1-deficient Th17 cells have a defect in IL-9 expression (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the HTLV-transformed cell line Hut-102 has an IL-9-producing Th17 phenotype. It is shown that in this cell, specific knockdown of NF-B protein c-Rel results in reduced IL-9 production (77). We have also found that NFAT1-deficient Th17 cells have a defect in IL-9 expression (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…Likewise, IRF4 was found to be constitutively expressed in ATL as opposed to nonlymphocytic HTLV-1 infection (48). A number of studies have linked activating mutations and high levels of expression of IRF4 with HTLV-1 infection, with IRF4 expression resulting in reduced expression levels of genes previously shown to be dysregulated in ATL cases (48)(49)(50)(51)(52)(53). As proviral integration was found in the 5= ends of both of these genes, it is possible that integration may alter gene expression and thus may have contributed to transformation or ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell lysates were prepared as described previously (19). Cell lysates were resolved by SDS-PAGE and transferred to an Immobilon-P nylon membrane (EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%